2014
DOI: 10.1007/s10120-014-0348-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of cancer-related pathways affected by genetic and epigenetic alterations in gastric cancer

Abstract: Background The profiles of genetic and epigenetic alterations in cancer-related pathways are considered to be useful for selection of patients likely to respond to specific drugs, including molecular-targeted and epigenetic drugs. In this study, we aimed to characterize such profiles in gastric cancers (GCs).Methods Genetic alterations of 55 cancer-related genes were analyzed by a benchtop next-generation sequencer. DNA methylation statuses were analyzed by a bead array with 485,512 probes. Results The WNT pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 39 publications
1
90
0
1
Order By: Relevance
“…Homeostasis of the gastrointestinal epithelium is 87 [47,[69][70][71][72][73][74][75]232] Fzd-3 [78] CTNNB1 [9,[88][89][90][91][92][93]96,97] LRP6 [228] TCF7L2 [98][99][100] PPN [79] CDH17 [80] EZH2 [81] HMGA1, HMGA2 [210,211] YY1 [86] TC1 (C8orf4) [201,202] miR-17-92 [161] mir-10a [168] has-miR-335 [166] hsa-miR-375 [163] Downregulation or function inhibition in gastric cancer Downregulation by hypermethylation Inactivation by miRNAs APC [145,146] APC [175] sFRP1, sFRP2, sFRP4, sFRP5 [78,96,149] AXIN2 [159] WIF-1 [144,149] EZF1 [78] Dkk-1, Dkk-2, Dkk-3 [59,144,148,…”
Section: Wnt/b-catenin Pathway In Gastric Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Homeostasis of the gastrointestinal epithelium is 87 [47,[69][70][71][72][73][74][75]232] Fzd-3 [78] CTNNB1 [9,[88][89][90][91][92][93]96,97] LRP6 [228] TCF7L2 [98][99][100] PPN [79] CDH17 [80] EZH2 [81] HMGA1, HMGA2 [210,211] YY1 [86] TC1 (C8orf4) [201,202] miR-17-92 [161] mir-10a [168] has-miR-335 [166] hsa-miR-375 [163] Downregulation or function inhibition in gastric cancer Downregulation by hypermethylation Inactivation by miRNAs APC [145,146] APC [175] sFRP1, sFRP2, sFRP4, sFRP5 [78,96,149] AXIN2 [159] WIF-1 [144,149] EZF1 [78] Dkk-1, Dkk-2, Dkk-3 [59,144,148,…”
Section: Wnt/b-catenin Pathway In Gastric Carcinogenesismentioning
confidence: 99%
“…In addition, Yu et al [148] showed by multivariate analysis that Dkk-3 methylation was associated significantly and independently with poor disease survival in gastric cancer, but not in colorectal cancer. Recently, DNA methylation status in 49 gastric cancer samples was analyzed by a bead array with 485512 probes [149] . This study revealed that the Wnt pathway was potentially activated by aberrant methylation of its negative regulators, such as Dkk-3, NKD1, Sox17, WIF-1 and sFRP1.…”
Section: Loss Of Wnt Repressor Function In Gastric Cancermentioning
confidence: 99%
“…Multiple experiments provided evidence indicating that mutations in exon 3 of CTNNB1 precipitates not only continuous activation of Wnt pathway but also multistep stomach carcinogenesis (67,68). Galectin-3, whose mutation locates at position 191, has been widely recognized equipped to substitute proline to histidine (gal-3H64), followed by increased nuclear accumulation of β-catenin as well as promotion of TCF transcription during gastric cancer evolvement (69).…”
Section: Wnt/β-catenin Pathway and Gastric Cancermentioning
confidence: 99%
“…29 A very recent publication even showed that in 4 out of 50 advanced gastric cancers, PIK3CA and PTPN11 were both mutated, leading to activation of the AKT pathway. 30 This seems to be more than just coincidence. It is known that in most cancers, there is not only one gene that is mutated, but a distinct set of genes.…”
Section: Ptpn11 Variant and Mcap Syndrome D Döcker Et Almentioning
confidence: 98%